2017
DOI: 10.3340/jkns.2017.0202.014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Uncinate Process Resection on Subsidence Following Anterior Cervical Discectomy and Fusion

Abstract: ObjectiveSubsidence is a frequent complication of anterior cervical discectomy and fusion. Postoperative segmental micro-motion, thought to be a causative factor of subsidence, has been speculated to increase with uncinate process resection area (UPR). To evaluate the effect of UPR on micro-motion, we designed a method to measure UPR area based on pre- and postoperative computed tomography images and analyzed the relationship between UPR and subsidence as a proxy of micro-motion.MethodsWe retrospectively colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
2
24
2
Order By: Relevance
“…Graft subsidence is one of the major complications of ACDF, which can result in foraminal stenosis, segmental kyphosis, pseudarthrosis, and adjacent segment disease 12) . The known risk factors of subsidence after ACDF are age, BMI, smoking history, low BMD 2)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Graft subsidence is one of the major complications of ACDF, which can result in foraminal stenosis, segmental kyphosis, pseudarthrosis, and adjacent segment disease 12) . The known risk factors of subsidence after ACDF are age, BMI, smoking history, low BMD 2)…”
Section: Discussionmentioning
confidence: 99%
“…, end plate preparation 15) , cage type 1,7,22) , location 21) , cervical alignment 13,14) , and a small degree of segmental instability 10,12,19,25) . Furthermore, Lee et al 14) suggested that the main surgical and patient factors affecting subsidence are cervical alignment, age, and use of plates system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most anterior cervical discectomy and fusion procedures include cervical uncosectomy or uncoforaminotomy to decompress nerve roots in patients with cervical radiculopathy, Lee DH et al reported that complete uncinate process resection (UPR) during ACDF improves pain in a patient's arm more rapidly than conventional ACDF without UPR and provides similar fusion rates [3,5]. Meanwhile, SH Lee et al reported that complete UPR over 38% during ACDF increases the risk of subsidence during follow up [4].…”
mentioning
confidence: 99%